2019
DOI: 10.1051/0004-6361/201834425
|View full text |Cite
|
Sign up to set email alerts
|

Polar flux imbalance at the sunspot cycle minimum governs hemispheric asymmetry in the following cycle

Abstract: Aims. Hemispheric irregularities of solar magnetic activity is a well-observed phenomenon, the origin of which has been studied through numerical simulations and data analysis techniques. In this work we explore possible causes generating north-south asymmetry in the reversal timing and amplitude of the polar field during cycle minimum. Additionally, we investigate how hemispheric asymmetry is translated from cycle to cycle. Methods. We pursued a three-step approach. Firstly, we explored the asymmetry present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Other authors have identified this persistence in asymmetry when integrated over a solar cycle (Li et al, 2001;Leussu et al, 2016). In this context of possible longer-term memory we note that Bhowmik (2019) found from observations that asymmetry in polar fluxes at sunspot minimum was reflected in sunspot asymmetry in the subsequent cycle. The paradox of random fluctuations generating long-term trends in sunspot asymmetry was modelled by Nepomnyashchikh et al (2019) who used random perturbations to tilt angle and yet generated trends that lasted several solar cycles.…”
Section: Cycle 19supporting
confidence: 61%
“…Other authors have identified this persistence in asymmetry when integrated over a solar cycle (Li et al, 2001;Leussu et al, 2016). In this context of possible longer-term memory we note that Bhowmik (2019) found from observations that asymmetry in polar fluxes at sunspot minimum was reflected in sunspot asymmetry in the subsequent cycle. The paradox of random fluctuations generating long-term trends in sunspot asymmetry was modelled by Nepomnyashchikh et al (2019) who used random perturbations to tilt angle and yet generated trends that lasted several solar cycles.…”
Section: Cycle 19supporting
confidence: 61%
“…However, two different proposals exist in the literature for the poloidal field generation-one involves the decay and dispersal of bipolar magnetic regions at the solar surface, termed as the Babcock-Leighton mechanism (Babcock 1961;Leighton 1969) and the other evokes strong helical turbulence inside the solar convection zone, known as the mean-field α effect (Parker 1955;Steenbeck et al 1966). In recent years, dynamo models based on the Babcock-Leighton mechanism have been successful in explaining different observational aspects regarding solar activity (Dikpati & Charbonneau 1999;Nandy & Choudhuri 2002;Choudhuri et al 2004;Nandy et al 2011;Choudhuri & Karak 2012;Bhowmik & Nandy 2018;Hazra & Nandy 2019;Bhowmik 2019). Recently, data-driven 2.5D kinematic dynamo models and 3D kinematic solar dynamo models have also been developed to study different observational aspects regarding solar activity (Brun 2007;Jouve et al 2011;Yeates & Muñoz-Jaramillo 2013;Hung et al 2017;Hazra et al 2017;Karak & Miesch 2017;Hazra & Miesch 2018;Kumar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We find the north-south asymmetry of filament numbers from the Meudon database is correlated with the north-south asymmetry of filament numbers from McIntosh data during the overlapping period with a Spearman rank correlation coefficient 0.50 with the confidence of 99.99%. This asymmetry in filament distribution may arise from the underlying asymmetry of magnetic field emergence associated with the solar dynamo mechanism (Passos et al 2014;Bhowmik 2019;Hazra & Nandy 2019) and (or) they might be related to hemispheric asymmetries in large-scale plasma flows (Lekshmi et al 2018(Lekshmi et al , 2019; these merit further theoretical investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of magnetic fields in the Sun is not symmetric in two hemispheres (Bhowmik 2019). Naturally features like sunspots, filaments, plages, etc., which are magnetic in nature show north-south asymmetry.…”
Section: Introductionmentioning
confidence: 99%